2005
DOI: 10.1002/cne.20604
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter phenotypes of intermediate zone reticular formation projections to the motor trigeminal and hypoglossal nuclei in the rat

Abstract: Numerous studies suggest an essential role for the intermediate (IRt) and parvocellular (PCRt) reticular formation (RF) in consummatory ingestive responses. Although the IRt and PCRt contain a large proportion of neurons with projections to the oromotor nuclei, these areas of the RF are heterogeneous with respect to neurotransmitter phenotypes. Glutamatergic, GABAergic, cholinergic, and nitrergic neurons are all found in the PCRt and IRt, but the projections of neurons with these phenotypes to the motor trigem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
105
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 81 publications
(106 reference statements)
7
105
1
Order By: Relevance
“…This drive is mainly glutamatergic (11,58), consistent with the evidence that many IRt XII premotor neurons use glutamate as their main transmitter (61). Other than that, little is known about the neurochemical features of IRt XII premotor neurons.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…This drive is mainly glutamatergic (11,58), consistent with the evidence that many IRt XII premotor neurons use glutamate as their main transmitter (61). Other than that, little is known about the neurochemical features of IRt XII premotor neurons.…”
supporting
confidence: 67%
“…The medullary reticular formation has been shown previously to contain cholinergic neurons with axonal projections to the facial, trigeminal, and XII motor nuclei (13,14,61), but the incidence of such projections appeared to be relatively small. The cells retrogradely labeled from these nuclei were scattered widely, making it difficult to appreciate the potential importance of these projections.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The HMN controls GG muscle activity and is important for a variety of physiological functions including maintenance of airway patency, mastication, and swallowing. It has been known for more than a decade that the HMN receives nitrergic innervation (Pose et al 2005;Travers et al 2005), yet potential involvement of NO in HMN function remains obscure because there is limited evidence describing effects of NO on HMN activity in vivo. A study by Montero et al (2008) showed that microiontophoretic application of an NOS inhibitor or ODQ decreased inspiratory-related HMN activity, whereas injection of DEA or 8-BrcGMP did the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…The hypoglossal motor nucleus (HMN) is an ideal model system to study NO modulation of neuronal activity because 1) properties of hypoglossal motoneurons are well characterized (Rekling et al 2000); 2) the HMN receives nitrergic innervations (Pose et al 2005;Travers et al 2005); 3) hypoglossal motoneurons express sGC (Gonzalez-Forero et al 2007); and 4) short-term manipulation of NO/cGMP signaling in the HMN can modulate rhythmic output of the region (Montero et al 2008). These results provide compelling evidence that NO is an important modulator of hypoglossal motoneuron activity; however, our understanding of the role of NO in the HMN is far from complete.…”
mentioning
confidence: 99%